2019
DOI: 10.5114/wiitm.2019.84702
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative and early postoperative complications in women with stress urinary incontinence treated with suburethral slings: a randomised trial.

Abstract: Introduction: The midurethral sling has become the current standard for the treatment of female stress urinary incontinence. Aim: To assess intraoperative complications, early post-operative complications as well as the efficacy of tension-free vaginal tape: retropubic and trans-obturator tape procedures. Material and methods: The analysis involved 91 tension-free vaginal tape (TVT) and 60 transobturator tape (TOT) procedures. Both groups were comparable in terms of patient characteristics, urodynamic results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
4
5
3
1
Order By: Relevance
“…The types of specific postoperative complications which occurred, and their frequency are similar to those described in the literature [3,6,10,15,16]. Affecting 41 women, urinary retention and voiding problems were the most frequent complications in our study.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The types of specific postoperative complications which occurred, and their frequency are similar to those described in the literature [3,6,10,15,16]. Affecting 41 women, urinary retention and voiding problems were the most frequent complications in our study.…”
Section: Discussionsupporting
confidence: 87%
“…In comparison to previous studies reporting low numbers of urinary tract infections, making up less than 5% of all complications [14,15] or not reporting a single one [10], our study showed ten urinary tract infections which make up 13.7% of the complications. Several further studies did not refer to urinary tract infections when discussing postoperative complications [16,17].…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations